Kompetensi, Beban Kerja terhadap Kinerja Karyawan dengan Disiplin Kerja sebagai Variabel Intervening - Suci Rahmawati; Ismartaya Ismartaya; Erny Amriani Asmin (IPM2KPE, 2024)
The purpose of this research is to determine employee responses and analyze the direct and indirect influence of competence and workload on employee performance with work discipline as an intervening variable at PT. Sun Star Prima Motor Tajur Bogor. This research uses path analysis data analysis techniques. Data testing used the SPSS version 22 program. The research results showed that employee responses to performance and competence were in the very good category, as well as employee responses to workload and work discipline were in the good category. Meanwhile, the results of hypothesis testing prove that competence and workload directly have a positive and significant effect on work discipline. Competence does not directly have a positive and significant effect on employee performance. Workload and work discipline directly have a positive and significant effect on employee performance. Meanwhile, competency and workload indirectly have a positive and significant effect on employee performance with work discipline as an intervening variable. Keywords: Workload, Work Discipline, Competence, Employee Performance